Anxiety from receiving news about covid-19: The role of character strength - Junaidin Junaidin; Nurulsani S. Abd Latif; Amalia S.J Kahar (Universitas Ahmad Dahlan, 2021)
The spread of covid-19 is happening in all countries, including Indonesia. The number of positive patients in Indonesia continues to increase. Whereas the news related to covid-19 informed by various media tend to cause psychological disorders, including anxiety. The strength of character is one of the individual capacity to prevent anxiety. Therefore, this study aimed to examine the effect of character strength on anxiety when receiving the covid-19 news. Four hundred sixty-one participants that have been chosen through snowball sampling, involved in this study. Data were collected with Character Strength Scale and Hamilton Anxiety Rating Scale. Simple regression analysis was used to analyze the data. The results show that character strength significantly predict anxiety when participant receive news about Covid-19. Consideration in developing character strength is needed to reduce anxiety during pandemic covid-19.